Hydrogen production by thermo-catalytic conversion of methane over lanthanum strontium cobalt ferrite (LSCF) and αAl2O3 supported Ni catalysts - Ayodele, Bamidele V.; Mohamed Yazrul, Mohd Yassin; Rosmawati, Naim; Sureena, Abdullah (Elsevier Ltd., 2019)
This study investigates hydrogen production by thermo-catalytic steam methane reforming over lanthanum strontium cobalt ferrite supported Nickel (Ni/LSCF) and commercial Ni/αAl2O3 catalysts. The Ni/LSCF catalyst was synthesized using wet impregnation method and characterized by XRD, TEM, SEM, EDX, N2-physisorption analysis, and H2-TPR. The characterization analyses show that Ni/LSCF and Ni/αAl2O3 possess the required physicochemical properties to catalyze the steam methane reforming reaction. The activity of the Ni/LSCF catalyst in steam methane reforming at 750 °C, 800 °C, and 850 °C resulted in CH4 conversions of 73.46%, 78.67%, and 87.56%, respectively. In addition, hydrogen (H2) yields of 64.34%, 72.57%, and 82.56% were obtained from the steam methane reforming at 750 °C, 800 °C, and 850 °C, respectively over the Ni/LSCF catalyst. The Ni/LSCF catalyst was found to have higher activities in term of CH4conversion and H2 yield compare to the commercial Ni/αAl2O3. However, the stability test conducted at 480 min time on stream (TOS) revealed that the commercial Ni-αAl2O3 was more stable in the steam methane reforming than the Ni/LSCF catalyst. The characterization of the used catalysts by TEM, XRD and TGA shows evidence of carbon deposition mostly on the used Ni/LSCF catalyst.